Disaster Mitigation Study in School Prone to Earthquake and Tsunami Disaster (Case Study Of SMAN 4 Pariaman) - Maharani, Suci; Erianjoni, Erianjoni (Science and Environmental Journal for Postgraduate, 2020)
SMAN 4 Pariaman is located in an area prone to disasters, especially the earthquake and tsunami. SMAN 4 Pariaman is located on the coast of the West Coast of Sumatra, which belongs to the tsunami red zone in Pariaman City. Based on this, all school residents must be prepared to face the disasters that will occur, especially the earthquake and tsunami. This type of research is a combination of research (Mixed Methods). This research is a step of research by combining two pre-existing forms of research namely qualitative research and quantitative research. The results of the study found 5 main priorities, namely 1) Optimization of meeting the basic needs of disaster management with a value of (5,000), 2) Application of evacuation routes and zones of vulnerability to our position or presence (4,556), 3) Socialization through facilities and infrastructure prepared by parties BPBD with grades (4,412), 4) Make maps to the evacuation sites of schools with grades (4,200), 5) Facilitate evacuation route signs such as posters with grades (3,587). The results of the FGD and data processing by data processing with Bayes method obtained 5 main priorities, namely 1) Schools must incorporate knowledge about disasters into the curriculum or subjects with values ??(5,100), 2) Improvement of earthquake resistant facilities (4,467), 3) Schools must enter disaster mitigation activities into extracurricular values ??(3,933), 4) Making maps of tsunami evacuation routes to TES with values ??(3,923), 5) Conduct TRC education and training with a value of 3,857.